Measuring the End of Life Premium in Cancer using Individual ex ante Willingness to Pay - Sara Olofsson; Ulf-G. Gerdtham; Lars Hultkrantz; Ulf Persson (Lund University, School of Economics and Management, Department of Economics, 2016)
For the assessment of value of new therapies in healthcare, Health Technology Assessment (HTA) agencies often review the cost per Quality-Adjusted Life-Years (QALY) gained. Some HTAs accept a higher cost per QALY gained when treatment is aimed at prolonging survival for patients with a short expected remaining lifetime, a so called End-Of-Life (EoL) premium. The objective of this study is to elicit the existence and size of an EoL premium in cancer. Data was collected from 509 individuals in the Swedish general population 20-80 years old using a web-based questionnaire. Preferences were elicited using subjective risk estimation and the contingent valuation (CV) method. A split-sample design was applied to test for order bias. The value of a QALY at EoL in cancer was between exteuro275,000 and exteuro440,000, which is higher than the thresholds applied by HTAs. When expected remaining life expectancy was 6 months, the value of a QALY was 10-20 % higher compared to when remaining life expectancy was 24 months. Order of scenarios did not have a significant impact on the result and the result showed scale sensitivity. Thus this study supports an EoL premium in cancer when expected remaining lifetime is short.
Keywords: D61; D80; I18; J17; 330; willingness to pay; value of a QALY; cancer; contingent valuation; order bias